2010 IEEE International Geoscience and Remote Sensing Symposium 2010
DOI: 10.1109/igarss.2010.5650889
|View full text |Cite
|
Sign up to set email alerts
|

Towards Bayesian estimator selection for QuikSCAT wind and rain estimation

Abstract: The QuikSCAT scatterometer infers wind vectors over the ocean using measurements of the surface backscatter. During rain events the QuikSCAT observations are subject to rain contamination. Three separate estimators have been developed: wind-only, simultaneous wind and rain, and rain-only, which account for rain contamination in varying degrees. This paper introduces a Bayes estimator selection technique to adaptively choose a best estimator from among the three types of estimators at each measurement location.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is found that there is a good correlation between the quality control flag and rain flag, which has a certain reference value in judging whether there is rain [8][9][10]. The third strategy obtains information data by matching external data and then extends rain as an independent variable to the geophysical model function (GMF) so that the new GMF can also consider the influence of rain [11][12][13][14][15][16][17]. The fourth approach is to study the transmission process and scattering characteristics of microwaves on rainy days and then construct the microwave radiation transmission model under rainy conditions, which can correct the influence of rain on the wind measurement [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that there is a good correlation between the quality control flag and rain flag, which has a certain reference value in judging whether there is rain [8][9][10]. The third strategy obtains information data by matching external data and then extends rain as an independent variable to the geophysical model function (GMF) so that the new GMF can also consider the influence of rain [11][12][13][14][15][16][17]. The fourth approach is to study the transmission process and scattering characteristics of microwaves on rainy days and then construct the microwave radiation transmission model under rainy conditions, which can correct the influence of rain on the wind measurement [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%